2019
DOI: 10.21873/invivo.11685
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mofettes on Oxidative Stress/Antioxidant Balance in Experimental Myocardial Ischemia

Abstract: Background/Aim: Natural mofettes are gases resulting from post-volcanic emanations. This study aimed to examine the effect of mofette therapy on plasma oxidative stress and antioxidant parameters in rats after experimental induction of myocardial ischemia, as well as on structural changes in myocardial tissue. Materials and Methods: White Wistar-Bratislava rats were divided into three groups. In groups 2 and 3, myocardial ischemia was induced by isoproterenol. Rats in group 3 were additionally exposed to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The animals from groups 2–4 subcutaneously received a single dose of ISO (45 mg/kg) on day 14 of the experiment. The dose that was used was previously tested and considered the minimal dose producing acute myocardial infarction with elevation of cardiac enzymes, such as troponin [ 3 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…The animals from groups 2–4 subcutaneously received a single dose of ISO (45 mg/kg) on day 14 of the experiment. The dose that was used was previously tested and considered the minimal dose producing acute myocardial infarction with elevation of cardiac enzymes, such as troponin [ 3 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peroxidation of PUFAs on cell membranes alters cell membrane transport mechanism, membrane channel function and membrane receptor interactions (1). In earlier studies MDA biomarker has been used to show the connection between oxidative stress and chronic obstructive pulmonary disease (COPD) (19), lumbar disc degeneration (LDD) (20), myocardial ischemia (21) and diabetes mellitus (DM) (22). A review by Sardaro et al (6) concluded that association between the most frequent inflammatory, potentially malignant diseases is well established.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al 2018 (19) studied the effect of oligomeric proanthocyanidin (OPC) (23) on the oxidative stress and lung function in COPD patients. The results showed that OPC supplementation significantly reduced the plasma SOD and MDA biomarker concentrations and the OPC supplementation was effective in increasing the antioxidant (21) studied the effect of mofettes which are gases resulting from natural post-volcanic emnations that are found in certain areas of Romania. They used Wistar-Bratislava rats divided into three groups: 1, control group; 2, isoproterenolinduced myocardial ischemia group; 3, isoproterenol-induced myocardial ischemia+mofette group.…”
Section: Discussionmentioning
confidence: 99%
“…During therapy, CO2 inhaled and dissolved in plasma, and absorbed into the skin, has many effects on the body; thus, at the level of peripheral circulation, it induces skin hyperemia by direct action on metarterioles, with an increase in skin temperature by 1.5-4 degrees C and a 44% increase in skeletal muscle blood flow. There are also effects on cardiac hemodynamics by causing arterial vasodilation, a decrease in the pre-ejection period, an increase in the ejection period, and a reduction in blood pressure with consequences on peripheral oxygen use, which explains the improvement of cardiac performance parameters as well as the exercise capacity in coronary patients and patients with myocardial infarction sequelae (12). The mofettes used for therapeutic purposes in Romania, in the Hospital of Rehabilitation in Cardiovascular diseases Covasna, are unique in the world.…”
Section: Relevant Data Regarding Natural Therapeuticmentioning
confidence: 99%